2.3x= 10x312+ 8.274
2.3x=10.312+8.274
\(2.3^x=10.3^{12}+8.\left(3^3\right)^4\)
\(2.3^x=10.3^{12}+8.3^{12}\)
\(2.3^x=3^{12}.\left(10+8\right)\)
\(2.3^x=3^{12}.18\)
\(3^x=3^{12}.18:2\)
\(3^x=3^{12}.9\)
\(3^x=3^{12}.3^2\)
\(3^x=3^{14}\)
\(\Rightarrow x=14\)
2.3x=10.312+8.274
2.3x=10.312+23.312
2.3x=312.18
2.3x=312.32.2
2.3x=314.2
=>x=14
2.3x =10.312 +8.274
tìm x
\(\Rightarrow6x=5312\)
\(\Rightarrow x=5312:6\)
\(\Rightarrow x=885,3333333\)
tíc nha
\(2.3x=10.312+8.274\)
\(=2.3x=3120+2192\)
\(2.3x=5312\)
\(3x=5312:2\)
\(3x=2656\)
\(x=2656:3\)
\(x=\frac{2556}{3}\)
2.3x=10.312+ 8.274
làm giùm mình với ạ mình đang cần gấp
\(2\cdot3^x=10\cdot3^{12}+8\cdot27^4\)
\(\Rightarrow2\cdot3^x=10\cdot3^{12}+8\cdot\left(3^3\right)^4\)
\(\Rightarrow2\cdot3^x=10\cdot3^{12}+8\cdot3^{12}\)
\(\Rightarrow2\cdot3^x=18\cdot3^{12}\)
\(\Rightarrow3^x=\dfrac{18\cdot3^{12}}{2}\)
\(\Rightarrow3^x=9\cdot3^{12}\)
\(\Rightarrow3^x=3^2\cdot3^{12}\)
\(\Rightarrow3^x=3^{14}\)
\(\Rightarrow x=14\)
BT1 : Tìm x biết :
a, (7x - 11)3 = 25.52 + 200
b, 720 : (41 - ( 2x - 5 )) = 23.5
c, 2.3x = 10.312 + 8.274
Bài 1: Tìm x
a) Ta có: \(\left(7x-11\right)^3=2^5\cdot5^2+200\)
\(\Leftrightarrow\left(7x-11\right)^3=32\cdot25+200=1000\)
\(\Leftrightarrow7x-11=10\)
\(\Leftrightarrow7x=21\)
hay x=3
Vậy: x=3
b) Ta có: \(720:\left(41-\left(2x-5\right)\right)=2^3\cdot5\)
\(\Leftrightarrow720:\left(41-2x+5\right)=8\cdot5=40\)
\(\Leftrightarrow-2x+46=18\)
\(\Leftrightarrow-2x=18-46=-28\)
hay x=14
Vậy: x=14
c) Ta có: \(2\cdot3^x=10\cdot3^{12}+8\cdot27^4\)
\(\Leftrightarrow2\cdot3^x=10\cdot3^{12}+8\cdot3^{12}\)
\(\Leftrightarrow2\cdot3^x=18\cdot3^{12}\)
\(\Leftrightarrow3^x=\dfrac{18\cdot3^{12}}{2}=9\cdot3^{12}\)
\(\Leftrightarrow3^x=3^2\cdot3^{12}=3^{14}\)
hay x=14
Vậy: x=14
A (7x-11)3=25.52+200
(7x-11)3=800+200
(7x-11)3=1000
(7x-11)3=103
7x-11=10
7x=10+11
7x=21
x=21:7
x=3
B 720:(41-(2x-5))=23.5
720:(41-(2x-5))=40
41-(2x-5)=720:40
41-(2x-5)=18
2x-5=41-18
2x-5=23
2x=23+5
2x=28
x=28:2
x=14
C 2.3x=10.312+8.274
2.3x=10.312+8.(33.4)
2.3x=10.312+8.312
2.3x=312.(10+8)
2.3x=312.18
3x=( 312.18):2
3x=312.9
3x=312 .32
3x=314
3x=14
x=14
4x+2.3x=16.125
`4^(x+2) .3^x = 16.12^5`
`4^(x+2) .3^x = 4^2 . (3.4)^5`
`4^(x+2) .3^x = 4^2 . 3^5. 4^5`
`4^(x+2) .3^x = 4^7 . 3^5`
`4^(x+2) .3^x = 4^(5+2) . 3^5`
`x=5`
Ta có:4x+2.3x=16.125
⇔ 4x+2.3x=417.315
⇔ 4x+2:417.3x:315=1
⇔ 4x-15.3x-15=1
⇔ 12x-15=120
⇔ x-15=0
⇔ x=15
Ta có: \(4^{x+2}\cdot3^x=16\cdot12^5\)
\(\Leftrightarrow4^x\cdot16\cdot3^x=16\cdot12^5\)
\(\Leftrightarrow12^x=12^5\)
hay x=5
2.3x+3=10.312 + 8.312
\(2.3^{x+3}=10.3^{12}+8.3^{12}\)
\(\Leftrightarrow2.3^{x+3}=18.3^{12}\)
\(\Leftrightarrow3^{x+3}=9.3^{12}\)
\(\Leftrightarrow3^{x+3}=3^{14}\)
\(\Leftrightarrow x+3=14\Leftrightarrow x=11\)
\(\Leftrightarrow2\cdot3^{x+3}=3^{12}\cdot18\\ \Leftrightarrow2\cdot3^{x+3}=3^{14}\cdot2\\ \Leftrightarrow x+3=14\Leftrightarrow x=11\)
2.3x+3=10.312+8.3122.3x+3=10.312+8.312
=2.3x+3=18.312⇔2.3x+3=18.312
=3x+3=9.312⇔3x+3=9.312
=3x+3=314⇔3x+3=314
=x+3=14⇔x=11
2.3x + 5.3x + 1 = 153
\(2.3^x+5.3^x.3=153\Leftrightarrow2.3^x+15.3^x=153\)
\(\Leftrightarrow17.3^x=153\Leftrightarrow3^x=9\Leftrightarrow x=2\)
\(\Leftrightarrow2.3^x+5.3.3^x=153\)
\(\Leftrightarrow17.3^x=3^2.17\)
\(\Leftrightarrow3^x=3^2\Rightarrow x=2\)
2.3x=10.312+8.274
mình thêm nhé
2.3x=10.312+8.274
2.3x=10.312+23.312
2.3x=312.18
2.3x=312.32.2
2.3x=314.2
=>x=14
4.3x+2 − 2.3x+1 = 810
Ta có: \(4.3^{x+2}-2.3^{x+1}=810\)
\(4.3^{x+1}.3-2.3^{x+1}=810\)
\(2.3^{x+1}\left(2.3-1\right)=810\)
\(2.3^{x+1}.5=810\)
\(3^{x+1}=81=3^4\)
x+1=4
x=3
2.3x+1 = 10. 312 + 8. 312
\(2.3^{x+1}=10.3^{12}+8.3^{12}\\ VP=\left(10+8\right).3^{12}=18.3^{12}=2.3^2.3^{12}\\ =2.3^{2+12}=2.3^{14}\\ VT=VP\\ \Rightarrow2.3^{x+1}=2.3^{14}\\ \Rightarrow x+1=14\\ Vậy:x=14-1=13\)
2.3ˣ⁺¹ = 10.3¹² + 8.3¹²
2.3ˣ⁺¹ = 3¹².(10 + 8)
2.3ˣ⁺¹ = 3¹².18
3ˣ⁺¹ = 3¹².18 : 2
3ˣ⁺¹ = 3¹².9
3ˣ⁺¹ = 3¹².3²
3ˣ⁺¹ = 3¹⁴
x + 1 = 14
x = 14 - 1
x = 13
\(2\cdot3^{x+1}=10\cdot3^{12}+8\cdot3^{12}\\\Rightarrow 2\cdot3^{x+1}=3^{12}\cdot(10+8)\\\Rightarrow 2\cdot3^{x+1}=3^{12}\cdot18\\\Rightarrow 2\cdot3^{x+1}=3^{12}\cdot3^2\cdot2\\\Rightarrow 3^{x+1}=3^{12}\cdot3^2\\\Rightarrow 3^{x+1}=3^{14}\\\Rightarrow x+1=14\\\Rightarrow x=14-1\\\Rightarrow x=13\\Vậy:x=13\)